ANALISIS DAN STRATEGI RENCANA TATA RUANG WILAYAH KABUPATEN INTAN JAYA - Verdy Sumbung; Harmonis Rante; Dewi Ana Rusim (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
Intan Jaya Regency is a new autonomous region resulting from the division of Paniai Regency in 2008 with an area of 8,000 km2. The issue of regional development and its infrastructure really needs to be taken seriously. The potential for regional development includes tourism areas, forest cultivation areas, agricultural cultivation areas and plantations. This study aims to identify, analyze the condition of the regional potential and the strategy for the preparation of the Regional Spatial Plan of Intan Jaya Regency. The study used primary and secondary data which were analyzed qualitatively method. The results shown that the condition of the regional potential and the available data were very adequate. The strategy to compiling the Regional Spatial Plan of Intan Jaya Regency includes legal strategies, development of tourism areas, development of agricultural and plantation cultivation areas, handling of disaster-prone areas, public services and aspects of regional competitiveness.